Bronsted acid catalyzed enantioselective pericyclic reactions - Sleet, Christopher E.; Tambar, Uttam K.; Maity, Pradip (Tetrahedron, 2017)
Pericyclic reactions can be challenging processes to render asymmetric, due to the concerted and non polar nature of the transition states. Several examples have been reported in which a suitable catalyst binds to a heteroatom-containing substituent in the substrate and accelerates the reaction rate. The requirement of coordinating functionalized substrates has limited the generality of such asymmetric transformations. Multifunctional Bronsted acids are promising catalysts that represent a new paradigm in asymmetric pericyclic reactions. These chiral catalysts rely on multiple non-covalent interactions in the transition state for asymmetric induction, which has been utilized to activate more general substrate classes. In this review, we will cover recent advances in Bronsted acid catalyzed pericyclic reactions and discuss the impact of catalyst design on the expansion of substrate scope for highly enantioselective processes. (C) 2017 Elsevier Ltd. All rights reserved.

Transition metal, azide, and oxidant-free homo- and heterocoupling of ambiphilic tosylhydrazones to the regioselective triazoles and pyrazoles - Panda, Subhankar; Maity, Pradip; Manna, Debasis (Organic Letters, 2017)
With N-tosylhydrazone as an ambiphilic reagent, an unprecedented cyclization reaction of two identical or different tosylhydrazones has been developed to access various 4,5-disubstituted-2H-triazoles under transition metal, azide, and oxidant-free conditions. A mechanistic.rationalization study led to the identification of several electronically diverse unsaturated systems for regioselective synthesis of 1- and 2-substituted 1,2,3-triazoles and pyrazoles.

Organocatalyst bound -aminoalkyl radical intermediate for controlled aerobic oxidation of iminium ions - Motaleb, Abdul; Bera, Asish; Maity, Pradip (Organic & Biomolecular Chemistry, 2018)
A catalyst bound -aminoalkyl radical intermediate from iminium is developed to control its formation and reactivity with aerobic oxygen. The influence of the catalyst was demonstrated via the ease of radical intermediate formation and its subsequent reactivity, including the first catalyst-controlled enantioselective aerobic oxidation with a chiral phosphite catalyst.

Removable functional group strategy for regiodivergent Wittig rearrangement products - Alam, Md Nirshad; Lakshmi, K. M.; Maity, Pradip (Organic & Biomolecular Chemistry, 2018)
1,2] and [2,3] Wittig rearrangements are competing reaction pathways, often leading to uncontrollable product distribution. We employ a single removable functional group to fulfill the dual role of attaining a reversible [2,3] and stabilizing radical intermediate for the [1,2] path to obtain both the Wittig products selectively for a broad range of substrates.

Allenoate prenucleophiles: a triply diastereoselective approach to beta-hydroxy esters containing all-carbon alpha-quaternary centers - Maki, Samantha L.; Maity, Pradip; Dougherty, Shannon; Johns, Jennifer; Lepore, Salvatore D. (Organic Letters, 2019)
Allenyl esters activated by titanium(IV) underwent additions to a wide range of aldehydes in high regio- and diastereoselectivities leading to products containing an all carbon quaternary center bearing an alpha-vinyl group that was installed with high selectivity for the Z-geometry. An aldol product was also converted to an indanone offering a new route to this important compound class. Product triple diastereoselectivity has been rationalized using a concerted transition-state model.

Phosphite-Catalyzed C-H allylation of azaarenes via an enantioselective [2,3]-Aza-wittig rearrangement - Motaleb, Abdul; Rani, Soniya; Das, Tamal; Gonnade, Rajesh G.; Maity, Pradip (Angewandte Chemie-International Edition, 2019)
A phosphite-mediated [2,3]-aza-Wittig rearrangement has been developed for the regio- and enantioselective allylic alkylation of six-membered heteroaromatic compounds (azaarenes). The nucleophilic phosphite adducts of N-allyl salts undergo a stereoselective base-mediated aza-Wittig rearrangement and dissociation of the chiral phosphite for overall C-H functionalization of azaarenes. This method provides efficient access to tertiary and quaternary chiral centers in isoquinoline, quinoline, and pyridine systems, tolerating a broad variety of substituents on both the allyl part and azaarenes. Catalysis with chiral phosphites is also demonstrated with synthetically useful yields and enantioselectivities.

[1,3]-Claisen rearrangement via removable functional group mediated radical stabilization - Alam, Md Nirshad; Dash, Soumya Ranjan; Mukherjee, Anirban; Pandole, Satish; Marelli, Udaya Kiran; Vanka, Kumar; Maity, Pradip (Organic Letters, 2021)
A thermal O-to-C [1,3]-rearrangement of alpha-hydroxy acid derived enol ethers was achieved under mild conditions. The 2-aminothiophenol protection of carboxylic acids facilitates formation of the [1,3] precursor and its thermal rearrangement via stabilization of a radical intermediate. Experimental and theoretical evidence for dissociative radical pair formation, its captodative stability via aminothiophenol, and a unique solvent effect are presented. The aminothiophenol was deprotected from rearrangement products as well as after derivatization to useful synthons.

Phosphite mediated asymmetric N to C migration for the synthesis of chiral heterocycles from primary amines - Rani, Soniya; Dash, Soumya Ranjan; Bera, Asish; Alam, Md Nirshad; Vanka, Kumar; Maity, Pradip (Chemical Science, 2021)
A phosphite mediated stereoretentive C-H alkylation of N-alkylpyridinium salts derived from chiral primary amines was achieved. The reaction proceeds through the activation of the N-alkylpyridinium salt substrate with a nucleophilic phosphite catalyst, followed by a base mediated [1,2] aza-Wittig rearrangement and subsequent catalyst dissociation for an overall N to C-2 alkyl migration. The scope and degree of stereoretention were studied, and both experimental and theoretical investigations were performed to support an unprecedented aza-Wittig rearrangement-rearomatization sequence. A catalytic enantioselective version starting with racemic starting material and chiral phosphite catalyst was also established following our understanding of the stereoretentive process. This method provides efficient access to tertiary and quaternary stereogenic centers in pyridine systems, which are prevalent in drugs, bioactive natural products, chiral ligands, and catalysts.

Blue fluorescence of cyano-tryptophan predicts local electrostatics and hydrogen bonding in biomolecules - Haldar, Tapas; Chatterjee, Srijan; Alam, Md Nirshad; Maity, Pradip; Bagchi, Sayan (Journal of Physical Chemistry B, 2022)
Cyano-tryptophan is an unnatural fluorescent amino acid that emits in the visible region. Along with the structural similarity with tryptophan, the unique photophysical properties of this fluorophore make it an ideal probe for biophysical research. Herein, combining fluorescence spectroscopy, infrared spectroscopy, and molecular dynamics simulations, we show that the cyano-tryptophan's emission energy quantifies the underlying bond-specific noncovalent interactions in terms of the electric field. We further report the use of fluorophore's emission energy to predict its hydrogen bond characteristics. We demonstrate that combining experiments with molecular dynamics simulations can provide the hydrogen bonding status of the nitrile moiety. In addition, we report a method to differentiate between aqueous and nonaqueous hydrogen-bonding partners. Using a phenomenological approach, we demonstrate that the presence of the cyano-indole moiety is responsible for the distinct correlations between the fluorophore's emission and the electrostatic forces on the nitrile bond. As indole is a privileged scaffold for both native amino acids and nucleobases, cyano-indoles will have many multifaceted applications.

C-H functionalization of pyridines - Maity, Susmita; Bera, Asish; Bhattacharjya, Ayantika; Maity, Pradip (Organic & Biomolecular Chemistry, 2023)
Pyridine and its reduced form (piperidine) are the most common nitrogen heterocycles in FDA-approved drugs. Additionally, their presence in alkaloids, ligands for transition metals, catalysts, and organic materials with various properties makes them among the most important structural cores. Despite its importance, direct and selective functionalization of pyridine remains scarce due to its electron-poor nature and nitrogen coordination power. Instead, functionalized pyridine rings were primarily constructed from suitably substituted acyclic precursors. The focus on sustainable chemistry with minimum waste generation encourages chemists to develop direct C-H functionalization. This review summarizes different approaches to tackle the reactivity and regio- and stereoselectivity aspects for direct pyridine C-H functionalization.

Controlled synthesis of thermosensitive tunable porous film of (pNIPAM)-b-(PCL) copolymer for sustain drug delivery - Amgoth, Chander; Patra, Sukanya; Wasnik, Kirti; Maity, Pradip; Paik, Pradip (Journal of Applied Polymer Science, 2023)
There have been reports on different types of porous polymer films for various applications. The designing of such porous films with uniform properties is a challenging task. In this work, tunable porous thin films of poly(N-isopropylacrylamide) (pNIPAM) and polycaprolactone (PCL), that is, (pNIPAM)-b-(PCL) has been fabricated and its sustained drug delivery applications have been reported. First, the (pNIPAM)-b-(PCL) has been synthesized through the addition polymerization of pNIPAM and PCL. Then the synthesized (pNIPAM)-b(PCL) has been used to design porous thin film with varying temperatures without using any external template, below and above the lower critical solution temperatures (LCST) of pNIPAM. Pore size in (pNIPAM)-b-(PCL) films has been tuned by varying the temperature from similar to 10 to 40 degrees C. Then the developed thermosensitive porous film has been taken and seeded with the K562 (chronic myeloid leukemia blood cancer) and HepG2 (hepatocarcinoma) cells and the skin cancer cells (B16-F10) killing efficiency of anticancer drug (e.g., doxorubicin hydrochloride, DOX) loaded (pNIPAM)-b-(PCL) film has been studied. It is found that the DOX-loaded (pNIPAM)-b-(PCL) can efficiently kill the skin cancer cells. The porous polymer thin film reported in this work can be a versatile platform for the loading of drugs and it can be used for the various therapeutic applications.
Keywords: Biomaterials; Biomedical Applications; drug delivery systems; films; nanostructured polymers

Organophosphites: an addition to the arsenal of organocatalysts - Baral, Nilofar; Rani, Soniya; Saikia, Pinku; Maity, Pradip (European Journal of Organic Chemistry, 2023)
Organophosphites are nucleophilic in nature and can act as a good leaving group owing to the stability of the phosphite anion. This dual reactivity makes them good candidates for nucleophilic organocatalysis. However, phosphites were introduced only in 2004 as the umpolung catalyst for acylsilane substrates utilizing sequential Brook rearrangements. Very recently, phosphites have been reported to catalyze aza-rearrangements and radical reactions. In this review, we discuss the reactivity parameters to understand its lack of use, as well as the potential for catalysis.
Keywords: acylradical; azaacyl equivalent; cylanion; organocatalysis; phosphite

2-Pyridone-directed CuII-catalyzed general method of C(sp2)-H activation for C-S, C-Se, and C-N cross-coupling: easy access to aryl thioethers, selenide ethers, and sulfonamides and DFT study - Pati, Tanmay K.; Molla, Sabir Ali; Ghosh, Narendra Nath; Kundu, Mrinalkanti; Ajarul, Sk; Maity, Pradip; Khamrai, Uttam; Maiti, Dilip K. (Journal of Organic Chemistry, 2024)
We have demonstrated N-substituted 2-pyridones as an N,O-directing group for selective C(sp(2))-H-activated thiolation, selenylation, and sulfonamidation of ortho C-H bonds of benzamides. This method utilizes a cost-effective Cu(II)-salt catalyst instead of precious metal catalysts, achieving high yields, including gram-scale synthesis and excellent functional group tolerance. We applied this protocol to access 30 different compounds with high yields, demonstrating thiolation of fluorine-substituted benzamides as well. Density functional theory (DFT) calculations support the mechanism, including acetate-supported concerted metalation deprotonation (CMD) steps and the unique role of dimethyl sulfoxide (DMSO) solvent. The facile synthesis of pharmaceutically important sulfonamides and other compounds highlights the method's potential in chemistry and medicinal chemistry.

Anionic 5-endo-dig cyclizations: an experimental investigation of in-plane aromaticity involving a non-enolate carbanion nucleophile - Nugent, Kristina M.; Hintze, Silas Q.; Maity, Pradip; Lepore, Salvatore D. (Organic Chemistry Frontiers, 2025)
Cyclitive additions of aliphatic carbanions to non-electrophilic carbon-carbon triple bonds under mild, transition-metal-free conditions are described for the first time. These results confirm theoretical models that invoke in-plane aromaticity to predict the favorability of 5-endo-dig reactions in these systems. In contrast to related Conia-ene cyclizations (5-enolexo-endo-dig), our results generally led to cyclic and allene products in near parity ratios across a broad range of substrates, suggesting that cyclization may proceed via an early ambimodal transition state. Experimental results are presented with a view to refining existing mechanistic models for this growing class of alkyne reactions.

Phosphite mediated molecular editing via switch to meta-C-H alkylation of isoquinolines: emergence of a distinct photochemical [1,3] N to C rearrangement - Rani, Soniya; Ray, Anuj Kumar; Dewangan, Devendra Kumar; Patil, Nita Aruna Ramchandra; Aarthika, M.; Paul, Ankan; Maity, Pradip (Chemical Science, 2025)
The isoquinoline core is present in one of the largest subsets of bioactive natural products. The multifunctional isoquinoline core exerts diverse bioactivity, resulting in the development of numerous isoquinoline-based drugs and molecules that are currently under clinical trials. We developed a new approach for phosphite-mediated [1,2] alkyl migration for an overall ortho-C-H alkylation via N-alkylation of isoquinoline. Tuning the phosphite-mediated protocol to switch the site selectivity would expedite direct and diverse multi-C-H bond functionalization. We report a new approach starting with a simple N-alkylation of isoquinoline with sterically and electronically diverse alkyl bromides for their phosphite-mediated photochemical [1,3] N to C rearrangement followed by a rearomatization sequence that leads to meta-C-H (C4) alkylation. Combined experimental and computational studies unveiled the emergence of an unprecedented C-N bond cleavage pathway from the singlet excited state of the enamine-type intermediate. Our radical bond-cleavage pathway favors substituted alkyl group migration that complements the recently successful meta-alkylation methods with smaller and more reactive electrophiles. This switch in site selectivity via tuning the phosphite-mediated protocol resulted in sequential C-H difunctionalization of isoquinoline including regiodivergent ortho, meta-dialkylations of isoquinolines.

Rational design of reduced graphene oxide/TiO2/gold nanorod nanocomposite for complete degradation of polystyrene microplastics in wastewater - UshaVipinachandran, Varsha; Naveenkumar, K.; Haroon, Kabir Hussain Badagoppam; Ashokan, Indhumathi; Sinha, Arup; Maity, Pradip; Bhunia, Susanta Kumar (Advanced Sustainable Systems, 2025)
Our planet is being devoured by plastic consumption every day. Water, soil, and air are deliberately polluted by the ingredients of these nondegradable plastics. Extensive usage of plastic has serious consequences in the environment, wildlife, and human health. A comprehensive approach to eradicate plastics from the planet is therefore imperative. Herein, a ternary nanocomposite subsumed of reduced graphene oxide (rGO), titanium dioxide (TiO2), and gold nanorods (AuNRs) is synthesized and effectively deployed to remove plastics from water as well as degradation of polymer film by both chemically and photocatalytically. The hydrothermally prepared nanocomposite completely removes polystyrene molecules from water, and 1.2 mg of plastic degradation is observed during the photolysis. Conversely, chemical degradation pathway induces the weight loss of 10.7 mg. Both Plasmon-induced interfacial charge transfer transition (PICTT) and Plasmon-induced hot electron transfer (PHET) assist the formation of reactive oxygen species (ROS) that collectively degrades the polymer strands. The spectrochemical and microscopic studies validate the degradation studies with cautious conclusions.
Keywords: chemical degradation; Photocatalysis; plasmonic hot electron; polystyrene microplastics; Reduced graphene oxide

Unified photoredox-catalyzed aerobic oxidative dynamic kinetic asymmetric transformation for C-N atropoisomers mediated by chiral organophosphites - Saikia, Pinku; Aarthika, M.; Bhattacharjya, Ayantika; Maity, Susmita; Bajpai, Priyam; Bera, Asish; Saha, Arindam; Gonnade, Rajesh G.; Vanka, Kumar; Maity, Pradip (Organic Letters, 2025)
The synthesis of anilides with a chiral C(=O)-N axis has relied on direct installation of the chiral C(sp2)-N(sp2) bond or enantioselective modification of the peripheral groups. However, these methods are constrained by the size and type of functional groups compatible with each strategy. Herein, we report a dynamic kinetic asymmetric transformation (DYKAT) for the aerobic oxidation of iminium ions to access C(=O)-N axial chirality that addresses those limitations. Furthermore, it eliminates the need for any auxiliary functional groups, which enables us to develop a unified method for the synthesis of atroposelective isoquinolone, lactam, and amide.

Mild and site-selective nucleophilic C-H functionalization of pyridines via its stable N-alkylated salts - Baral, Nilofar; Saikia, Pinku; Molla, Sabir Ali; Dewangan, Devendra Kumar; Maity, Pradip (Journal of the American Chemical Society, 2026)
Direct, site-selective C-H functionalization of pyridines offers an efficient approach to both streamlined synthesis and late-stage modification of bioactive and functional molecules. Existing approaches to direct nucleophilic substitution typically rely on highly reactive nitrogen-activating groups, which limit nucleophile scope and functional group tolerance and often suffer from poor site selectivity. Although milder activating groups address some of these limitations, they generally require additional installation and removal steps. Herein, we report a mild and general strategy employing designed alkyl halide activators that enables one-pot, site-selective functionalization of pyridines with synthetically valuable yet challenging nucleophiles. This strategy allows, for the first time, direct pyridine functionalization with a broad range of phosphites and amines, in addition to methoxide and cyanide. The mild and redox-neutral reaction conditions are particularly well suited for late-stage functionalization (LSF) of pharmaceutically relevant molecules, enabling site-selective modification with both phosphites and amines. The rational design of the alkyl halide activators, together with careful analysis of side-product formation, reveals the delicate balance required for success with electronically diverse nucleophiles and suggests broader applicability of this C-H functionalization strategy.